Teenager's attitude and behavior towards influencer advertising on body and diet in Peru - Montúfar-Calle, Álvaro (2024)
The early presence of adolescents in social networks (SN) and their prolonged exposure to influencer advertising, a non-invasive tactic focused on short-term advertising objectives with influencers as the digital advertising system's pillar, have placed them at risk. Evidence indicates hybridization in advertising (Feijoo et al., 2021; Feijoo, et al., 2023; Suárez-Álvarez and Pastor-Rodríguez, 2023) and limited capabilities of the adolescent to recognize advertising if it is not signaled (Evans et al., 2017; Feijoo et al., 2021; Martins et al., 2023; Zozaya Durazo et al., 2022; Zozaya-Durazo and Sádaba-Chalezquer, 2022). This prevents him from activating a critical attitude toward advertising (Evans et al., 2017; Feijoo et al., 2021; Feijoo et al., 2023; Zozaya Durazo et al., 2022). Therefore, it is essential to understand how they interact, perceive, and respond to influencer advertising in SR.   This study seeks to understand the response of Peruvian adolescents aged 11 to 17 years to influencer advertising on body and diet in SR, using a quantitative method, applying a representative survey to a sample of 1020 adolescents. The results indicate a significant volume of perceived advertising, and it is considered reasonable (52.25%), credible (45.91%), trustworthy (45.50%), and ethical (43.25%). They are the most valued leader dimension and a source of inspiration and motivation. The emotional response is positive and their attitude is receptive but less willing to interact. Finally, it is confirmed that the instructions and tips influence the attitude to see and read the content and the desire, likewise, the motivational phrases influence the intention to like it.